Pengaruh Pendampingan Dan Pelatihan Dinas Koperasi Usaha Kecil Dan Menengah Dan Tenaga Kerja Kabupaten Pesawaran Terhadap Pertumbuhan Usaha Mikro Dan Umkm Di Kecamatan Gedong Tataan Kabupaten Pesawaran - Rismawati, Reny; Sodirin , Sodirin (Utami Publisher, 2025)
MSMEs rely heavily on the economic growth of Pesawaran Regency as they play an important role in employment and innovation. However, MSMEs in this area face many problems, such as lack of capital, marketing issues, and lack of legal and management knowledge. As a result, the Office of Cooperatives, Small and Medium Enterprises (UMKM) and Manpower is crucial in providing assistance and training to MSME players to improve their capabilities in technology, marketing, and business management.The purpose of this descriptive quantitative research is to provide a comprehensive and accurate description of the characteristics of a particular population. Field research using a quantitative approach. In this study, 43 MSMEs established by the Pesawaran Regency Office of Small and Medium Enterprises Cooperatives and Manpower have been included. There are 1,036 MSMEs in this sample, with a 15% margin of error. The independent variables (X1) and training (X2) and the dependent variable (Y) are the growth of MSMEs and micro enterprises.